2020
DOI: 10.48550/arxiv.2007.03332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiability Properties of Log-Analytic Functions

Abstract: We show that the derivative of a log-analytic function is log-analytic. We prove that log-analytic functions exhibit strong quasianalytic properties. We establish the parametric version of Tamm's theorem for log-analytic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Theorem A is strong enough to obtain nice differentiability properties for loganalytic functions like non-flatness or a parametric version of Tamm's theorem (compare with [6]): With property (2) above one sees that theorem A coincides with Theorem 2.30 in [6], a preparation theorem for log-analytic functions on simple cells.…”
Section: Examplementioning
confidence: 94%
See 4 more Smart Citations
“…Theorem A is strong enough to obtain nice differentiability properties for loganalytic functions like non-flatness or a parametric version of Tamm's theorem (compare with [6]): With property (2) above one sees that theorem A coincides with Theorem 2.30 in [6], a preparation theorem for log-analytic functions on simple cells.…”
Section: Examplementioning
confidence: 94%
“…(2) Suppose that for every t ∈ π(C) there is d t ∈ R >0 ∪ {∞} such that C t = ]0, d t [ (such a cell C is called simple, compare with [6]). In [6] it is shown that Θ j = 0.…”
Section: Examplementioning
confidence: 99%
See 3 more Smart Citations